Flexibility System for Heilongjiang Power Grid Considering Carbon Reduction Targets - Liu, Qiang; Ban, Mingfei; Jiang, Haiyang; Liu, Yu; Xu, Hang; Guo, Jiangtao; Liu, Yiqi; Shi, Xingyu (Frontiers in Energy Research, 2022)
Enhancing the flexibility of power systems helps to balance the increasing renewable generation for achieving the rigid carbon reduction targets. The current flexible system in China can hardly meet the regulating demand of its ever-increasing renewable generation, especially in the Heilongjiang power grid (HPG), where the proportion of combined heat and power units that determine power generation by the heat requirement is enormous, while the peak shaving capacity in winter is limited. This research analyzes the necessity of establishing a new flexibility system for the HPG. Also, it introduces the new characteristics and the flexibility of the HPG. Then, it proposes classification and definition methods for the flexibility system of the HPG by referring to some similar power grids, e.g., the UK grid and the Danish grid. A simulation framework of power systems with flexibility enhancement is developed to perform quantitative evaluation of the HPG in different carbon reduction scenarios. The suggested flexibility system reorganizes and revises the principles of reserve classification, response time, and minimum reserve configuration. Simulation results verify the effectiveness of the proposed method through the measurement and analysis data of the HPG. This paper takes the HPG as an example to perform a quantitative analysis of the flexibility system. Also, it can provide tips and suggestions for other regions seeking carbon reductions.